Implementasi Metode Naive Bayes-Certainty Factor Untuk Identifikasi Cedera Pada Pemain Futsal - Rhiezky Arniansya; Nurul Hidayat; Ratih Kartika Dewi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
There are still many futsal players who think that injury can recover quickly without having to go through the right handling. There are injuries that injury can get worse if the initial handling is wrong. That's because the lack of understanding of players about injury. Injury treatment can be done by the physiotherapist but it was hit because of the lack of physiotherapist available for handling. In the research will be made an identification system to reduce these limitations by implementing the method of Naive Bayes-Certainty Factor-based android to diagnose the injury that affects futsal players. The results show that the use of Naive Bayes-Certainty Factor method has accurate results and a good and accurate diagnosis, since the output produced by the system has an accuracy of 88.57%. Hopefully with this application will be able to help the players futsal to know injury or handle injury and add insight about any injuries that can befall him.